The Effect of Career Development, Self-Efficacy, and Social Support on Employment Readiness, with Career Adaptability as a Mediating Variable, Among Fresh Graduates and Senior Undergraduates Without Work Experience - Khusnia Khusnia; Corry Yohana; Christian Wiradendi Wolor (International Journal Labs, 2026)
The transition from higher education to the labor market has become an increasingly important challenge in the Society 5.0 era, where graduates are required to possess not only academic knowledge but also adaptability, confidence, and career-related competencies. Many fresh graduates and final-year students without work experience continue to face difficulties in preparing for employment due to limited career planning, insufficient self-confidence, and inadequate support systems. This study aims to examine the effects of career development, self-efficacy, and social support on employment readiness, with career adaptability as a mediating variable among final-year students and fresh graduates without work experience. This research employed a quantitative approach using an explanatory research design. Data were collected through questionnaires distributed to respondents who met the research criteria and were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software. The results indicate that career development, self-efficacy, and social support have positive and significant effects on career adaptability and employment readiness. Furthermore, career adaptability was found to significantly influence employment readiness and mediate the relationships between career development, self-efficacy, social support, and employment readiness. These findings demonstrate that graduates’ readiness to enter the workforce is shaped not only by competency development and personal confidence but also by their ability to adapt to career changes. This study contributes theoretically by expanding the understanding of graduate employability models and provides practical implications for universities in designing effective career preparation programs to enhance graduate competitiveness in a dynamic labor market.